Mathematical Thinking Enhancement Program (MaTh-EP) / Nurul Akmal Md Nasir ... [et al.] - Md Nasir, Nurul Akmal; Singh, Parmjit; Narayanan, Geethanjali; Mohd Rasid, Nor Syazwani; Joseph, Boon Zik Hong (2021)
The present invention, called "Mathematical Thinking Enhancement Program (MaTh-EP)", generally relates to a program that enhances the development of mathematical thinking. This program is revolutionising from the problem-solving model from Polya (1973) and Schoenfeld (1992). This program integrates the problem-solving stages, heuristics, and metacognitive strategies instruction to guide students in solving non-routine problems that are intellectually challenging. This program is suitable for primary, secondary, and tertiary levels of education. Mathematics instructors, either at the school level or tertiary level, are encouraged to experience this program. The idea of MaTh-EP is to expose the participants to cognitive-metacognitive strategies and heuristics while solving non-routine problems. Non-routine problems are mostly concerned with developing participants' mathematical reasoning power and fostering an understanding that mathematics is a creative endeavour. MaTh-EP could develop participants thinking in Mathematics especially viewing mathematics problems related to the application in daily life. The potential program is suitable for students or instructors interested in booster their way of thinking in Mathematics.